Material science, engineering research, management and information technologies : selected, peer reviewed papers from the 4th International Conference on Engineering Materials, Energy, Management and Control (MEMC 2014), June 21-22, 2010, Wuhan, China - Zhao, X. J.; Jin, David; Zhang, Helen (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 2014 4th International Conference on Engineering Materials, Energy, Management and Control (MEMC2014), June 21-22, 2014, Wuhan, China. The 113 papers are grouped as follows: Chapter 1: Materials Science, Processing and Application, Chapter 2: Energy, Power and Heat Engineering, Chapter 3: Construction and Civil Engineering, Chapter 4: Environmental and Chemistry Engineering, Chapter 5: Control Engineering and Monitoring, Chapter 6: Design and Modeling in Mechanics and Construction Engineering, Chapter 7: Management, Computation and Informati.